Smooth time variation spectra as a tool to study line profile variability in spectra of hot stars - Sudnik, N.P. (Advances in Astronomy and Space Physics, 2012)
Line profiles in spectra of almost all OB stars are variable. In many cases the line profile variations are extremely weak (not more than 1% of the continuum level). For detection of such micro line profile variations of various nature we used a smooth Time Variation Spectra method (smTVS). This method appeared to be very sensitive and can be used to detect ultra weak line profile variations which can not be detected by other methods. We applied the smTVS method to detect the micro LPV in spectra of bright O stars λ Cep, λ Ori A and ζ Ori A. Spectra of these stars were obtained by using the 6-m and 1-m telescopes of the Northern Caucasus Special Astrophysical Observatory (Russia) and the 1.8-m telescope of Bohyunsan Astronomical Observatory (Korea).